Improving Marketing Skills Through Marketplace Platform Training for the Sunday Pahing Women's Group of Wotawati Village, Gunungkidul, Yogyakarta - NurSekti, Marita; Maolan, Muhammad; Noviana, Dini; Fauziah, Puji (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
In this evolving digitalization era, people are required to continue learning and be able to adapt to new environmental conditions, including business actors. The current digital era does not only touch education and communication, but also has a significant influence on product introduction and sales with fast and pragmatic approaches. MSME business actors in villages, for example, women's groups play an important role in the growth process of all sectors, one of which is the economic sector. To ensure the sustainability of MSMEs' potential to engage in the digitalization era, it is essential to offer support that enables women's groups to enhance their skills and self-reliance. The material presented to the target group covered the introduction of various marketplace platforms, product branding, and the use of one of the online marketplace Shopee. The activity was maximized by continuous assistance for women's groups to further explore the use of the marketplace Shopee.